The Impact of Bank Credit on Labor Reallocation and Aggregate Industry Productivity - BAI, JOHN (JIANQIU); CARVALHO, DANIEL; PHILLIPS, GORDON M. (Journal of Finance, 2018)
ABSTRACT We provide evidence that the deregulation of U.S. state banking markets leads to a significant increase in the relative employment and capital growth of local firms with higher productivity, and that this effect is concentrated among young firms. Using financial data for a broad range of firms, our analysis suggests that this effect is driven by a shift in the composition of local bank credit supply toward more productive firms. We estimate that this effect translates into economically important gains in aggregate industry productivity and that changes in the allocation of labor play a central role in driving these gains.